Corrosion evaluation and microstructural characteristics of 70/30 copper-nickel alloy fabricated by laser powder bed fusion - Mahdi Nadimi; Jie Song; Lin Cheng; Yao Fu (Journal of Alloys and Metallurgical Systems)
This study explored the fabrication of 70/30 Cu-Ni via LPBF technique and investigated its corrosion and microstructure properties. Samples were fabricated with varied parameters, including power, scan rate, and hatch spacing, and compared with wrought Cu-Ni alloy. Corrosion behaviour was conducted using cyclic polarization and EIS in 3.5 wt% NaCl. Optical microscopy and EBSD techniques were employed for microstructure evaluation. The results revealed that the examined LPBF samples had surface porosities below 1 %, indicating superior density and minimal voids, with larger grain sizes displaying elongated grain. Additionally, LPBF samples exhibited delayed breakdown passive layer potential, superior repassivation abilities compared to the wrought specimen. EIS analysis revealed corrosion resistance of as-fabricated samples was slightly higher than conventional ones, peaking at 58–73 kΩ.cm2 with hatch spacing between 125 and 200 μm and P/V ratio between 1.7 and 2 J/mm. However, deviation in parameters led to a decrease in corrosion resistance.